ANALYSIS THE IMPACT OF REFACTORING FROM MONOLITHIC APPLICATIONS TO MICROSERVICES ON RESPONSE TIME USING THE MDA AND SCA APPROACHES - Yusri, Shidqi Fadhlurrahman; Suwawi, Dawam Dwi Jatmiko; Adrian, Monterico (Informatika, Universitas Jenderal Soedirman, 2024)
This study investigates the impact of refactoring from a monolithic to a microservices architecture on application response time. Monolithic architecture, initially chosen for ease of development, faces scalability challenges as the application grows. Microservices offer a solution by enabling independent service deployment and enhanced scalability. This research uses Meta-Data Aided (MDA) and Static Code Analysis (SCA) methodologies to facilitate the refactoring process, applying them to the inventory-application project from a collaborative software development platform (GitHub). The refactoring involves decomposing the monolithic application, containerizing it with Docker, and evaluating performance using JMeter. Results show that microservices significantly reduce response time, particularly in API interaction tasks. While microservices improve scalability and flexibility, they require careful management of service communication. This research enhances understanding of the benefits of microservices in terms of response time and offers practical guidance for developers considering refactoring.